Pharmacological and Molecular Effects of Platinum(II) Complexes Involving 7-Azaindole Derivatives - Štarha, Pavel; Hošek, Jan; Vančo, Ján; Dvořák, Zdeněk; Suchý, Jr, Pavel; Popa, Igor; Pražanová, Gabriela; Trávníček, Zdeněk (PLOS ONE, 2014)
The in vitro antitumour activity studies on a panel of human cancer cell lines (A549, HeLa, G-361, A2780, and A2780R) and the combined in vivo and ex vivo antitumour testing on the L1210 lymphocytic leukaemia model were performed on the cis-[PtCl2(naza)2] complexes (1–3) involving the 7-azaindole derivatives (naza). The platinum(II) complexes showed significantly higher in vitro cytotoxic effects on cell-based models, as compared with cisplatin, and showed the ability to avoid the acquired resistance of the A2780R cell line to cisplatin. The in vivo testing of the complexes (applied at the same dose as cisplatin) revealed their positive effect on the reduction of cancerous tissues volume, even if it is lower than that of cisplatin, however, they also showed less serious adverse effects on the healthy tissues and the health status of the treated mice. The results of ex vivo assays revealed that the complexes 1–3 were able to modulate the levels of active forms of caspases 3 and 8, and the transcription factor p53, and thus activate the intrinsic (mitochondrial) pathway of apoptosis. The pharmacological observations were supported by both the histological and immunohistochemical evaluation of isolated cancerous tissues. The applicability of the prepared complexes and their fate in biological systems, characterized by the hydrolytic stability and the thermodynamic aspects of the interactions with cysteine, reduced glutathione, and human serum albumin were studied by the mass spectrometry and isothermal titration calorimetric experiments.